Employing peroxidase from Thai indigenous plants for the application of hydrogen peroxide assay - Kraingkrai Ponhong (2018)
© 2016, Iranian Chemical Society. Thai local plants known as banana stalk, banana blossom, banana, sugar-cane, oroxylum indicum fruit, sesbania grandiflora fruit, and pigeon pea fruit were utilized for screening peroxidase enzyme to replace costly horseradish peroxidase in the hydrogen peroxide assay. The highest peroxidase activity was found in banana stalk extracted solution. The kinetic parameters, i.e., Michaelis–Menten constant (Km) and maximum velocity (Vmax) of banana stalk peroxidase were carried out. The optimum pH and thermal stability of this enzyme were also studied. Furthermore, crude banana stalk peroxidase was applied for the determination of hydrogen peroxide in a disinfection solution without any purification. The influent parameters affecting the developed method were cautiously studied and optimized. The calibration curve of standard hydrogen peroxide was achieved between 2.0 and 10.0 μmol L−1 with correlation coefficient (r2) 0.995. The method validations of detection limit (LOD), limit of quantification (LOQ) and precision were investigated. The concentrations of hydrogen peroxide achieved by the developed method were correlated with the enzymatic method using commercial available horseradish peroxidase.